GEOCHEMICAL LANDSCAPES OF FERGANA CITY, THEIR SPECIFIC CHARACTERISTICS (Scientific journal of the Fergana State University, 2024)
The article describes the results of ecological and geochemical studies on the issues of zoning and classification of residential landscapes in the city of Fergana. The features of geochemical landscapes and the anthropogenic and technogenic load exerted on soils are analyzed.